Elaboración de un manual de Buenas Prácticas de Manufactura (BPM) en la empresa láctea San Enrique en la parroquia Mulaló. - Guayaquil Madril, Brayan Alexander (2019)
Because of product losses and increased competition, at "PROLASE" dairy company. This company seeks to provide healthy, safe and high quality products that satisfy with clients’ needs. The company in its cheese making section is located in 4 de October street and San Francisco of Mulaló parish, Latacunga canton, Cotopaxi province, this company has allowed to carry out this present integrating work that is based on the Elaboration of a handbook of Good Manufacturing Practices. This handbook is a guide that starts from the needs of the company based on real facts analyzed in detail. Through the checklist, the requirements of High Manufacturing Practices were analyzed. All the processes were focused on the needs and deficiencies that the company has to reduce or eliminate those parameters that did not meet the previous established diagnosis. For this reason, this handbook was developed, for the company "PROLASE" to improve or modify their operation processes, according to the regulations of the BPM, the manual will help as a tool aimed at all operational personnel of the company that has a direct or indirect relationship with the process of cheese making.